UPAYA MENINGKATKAN KOMPETENSI GURU MILITER DAN PELATIH DEPARTEMEN TAKTIK AKADEMI MILITER DI MAGELANG - Darwoyo, Darwoyo; Nugroho, Muhammad Awal Satrio; Sofiati, Sofiati (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The aim of this research is to find out why the competency of military teachers and trainers in the Tactics Department at the Military Academy still needs to be improved and to formulate efforts to improve the competency of military teachers and trainers in the Tactics Department at the Military Academy. The results of this research are the reason why the competency of military teachers and trainers in the Tactics Department of the Military Academy still needs to be improved because the implementation of the principles of training TNI AD personnel, namely the right man on the right place, is not yet optimal, there are still military teachers who have not participated in the education of teaching staff in the TNI AD environment, such as education: Educator Courses (Susgadik)/Military Teacher Courses (Susgumil)/ Training Officers (Patih), Military Teachers still have minimal education outside the military such as master's or doctoral levels, there are still military teachers who have not been able to utilize work facilities, and limited facilities and infrastructure. Efforts to increase the competency of military teachers and trainers in the Tactics Department at the Military Academy in managing learning, professional development by increasing guidance, counseling and direction in order to instill loyalty, obedience and obedience to Department of Defense personnel and their families towards Pancasila and the 1945 Constitution. Then the third effort is to increase academic mastery carried out based on increasing organic functional capabilities following Diklapa I, Diklapa II or Diktukpa Education, including training in order to maintain and improve the capabilities of Deptik personnel in accordance with programs from the Upper Command, General Development Education (Dikbangum) and Specialization Development Education and General Education as well as increasing support The 2023 Military Academy Cadet Education Operational budget for Department of Education material is supported by the Institute.